Merajut Kemandirian dengan Bimbingan Produksi dan Pemasaran Syariah Batik Ecoprint pada Kelompok Wanita Keluarga Pra Sejahtera di Loktabat Utara Banjarbaru: Building Self-Reliance through Sharia-Based Production and Marketing Guidance for Ecoprint Batik in Underprivileged Women’s Groups in Loktabat Utara, Banjarbaru - Erziaty, Rozzana; Zakiyah, Zakiyah; Wahab, Abdul; Al Hadi, M. Qoshid (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
The community empowerment program based on Nile tilapia cultivation using the biostimulant RAS system was expected to enhance participants' economic independence. Key challenges included limited access to information, education, and technology, alongside a lack of business management support. The program aimed to address these issues and positively impact the welfare of the disability community. Conducted under the title "Productive Efforts for Sensory (Hearing Impairment/Deafness) and Physical Disabilities through Nile Tilapia Cultivation Using a Circular Biostimulant RAS System in the Teras Inklusi Community," the activity used a Participatory Rural Appraisal (PRA) approach. The installation of circular RAS (Recirculating Aquaculture System) ponds in the field was completed as planned, with all system components, including circular ponds, filtration systems, and water distribution pipes, properly installed and functioning as expected. Effective coordination between the PKM team and partners resulted in no significant obstacles during installation. The training successfully enhanced participants' understanding and competencies, as evaluation results showed an increase in the "Good" category from 25% in the pre-test to 85% in the post-test, with no participants remaining in the "Poor" category after training.